Factors influencing Chinese university students' willingness to performing bystander cardiopulmonary resuscitation. (May 2017) - Lu, Cui; Jin, Ying-hui; Shi, Xiao-tong; Ma, Wen-jing; Wang, Yun-yun; Wang, Wei; Zhang, Yao
Highlights: Respondents who had previously performed bystander CPR were more willing to perform bystander CPR. Respondents who thought they had ability to perform CPR were more willing to perform bystander CPR. Respondents with higher self-perceived knowledge level of CPR were more willing to perform CPR. Abstract: Background and aim: Low rates of bystander-initiated CPR are a major obstacle to improved survival rates, and the aim of this study is to elucidate the factors associated with university students' attitudes toward performing bystander CPR. Methods: Questionnaires were distributed to 18 universities across three metropolises in China. One question asking for respondents' attitudes toward performing bystander CPR was set as the dependent variable, and the logistic regression models were used to extract independent factors for respondents' attitudes toward performing bystander CPR. Results: 2934 questionnaires were completed, with a response rate of 81.5%. Results suggested that predictors of willingness to perform bystander CPR were: previous experience of performing bystander CPR, higher self-perceived ability to perform bystander CPR properly after instruction, medicine and law discipline, male gender, not being the single child of their parents, higher participation in university societies, being used to taking decisive action immediately, less self-perceived life stress and higher self-perceived knowledge level of CPR. Conclusions: Persons having previous experience of performing bystander CPR and those who thought they would have the ability to perform bystander CPR properly are predominantly associated with willingness to perform bystander CPR. Psychological and cultural factors need further study.